Procyanidins Negatively Affect the Activity of the Phosphatases of Regenerating Liver - Stadlbauer, Sven; Rios, Pablo; Ohmori, Ken; Suzuki, Keisuke; Köhn, Maja (PLOS ONE, 2015)
Natural polyphenols like oligomeric catechins (procyanidins) derived from green tea and herbal medicines are interesting compounds for pharmaceutical research due to their ability to protect against carcinogenesis in animal models. It is nevertheless still unclear how intracellular pathways are modulated by polyphenols. Monomeric polyphenols were shown to affect the activity of some protein phosphatases (PPs). The three phosphatases of regenerating liver (PRLs) are close relatives and promising therapeutic targets in cancer. In the present study we show that several procyanidins inhibit the activity of all three members of the PRL family in the low micromolar range, whereas monomeric epicatechins show weak inhibitory activity. Increasing the number of catechin units in procyanidins to more than three does not further enhance the potency. Remarkably, the tested procyanidins showed selectivity in vitro when compared to other PPs, and over 10-fold selectivity toward PRL-1 over PRL-2 and PRL-3. As PRL overexpression induces cell migration compared to control cells, the effect of procyanidins on this phenotype was studied. Treatment with procyanidin C2 led to a decrease in cell migration of PRL-1- and PRL-3-overexpressing cells, suggesting the compound-dependent inhibition of PRL-promoted cell migration. Treatment with procyanidin B3 led to selective suppression of PRL-1 overexpressing cells, thereby corroborating the selectivity toward PRL-1- over PRL-3 in vitro. Together, our results show that procyanidins negatively affect PRL activity, suggesting that PRLs could be targets in the polypharmacology of natural polyphenols. Furthermore, they are interesting candidates for the development of PRL-1 inhibitors due to their low cellular toxicity and the selectivity within the PRL family.